Mediation resolving medical negligence litigation / Nurul Aini Yahya and Nur Atiqah Che Ismail - Yahya, Nurul Aini; Che Ismail, Nur Atiqah (Faculty of Law, 2012)
This project paper is a social-legal research study on the rights of people to initiate medical negligence claims in Malaysia. Currently, medical negligence litigation in Malaysia is regulated by the tort system in which the fault-based system is used. However, due to certain deficiencies which caused the fault-based system to become harsher since it demands a lot of money, time and obligation on the part of the victim to commence a claim, the system is now considered as inefficient to be used as a method to resolve medical negligence disputes. Hence, the most likely possible solution to overcome the harshness and difficulties that medical negligence victims have to go through to initiate a claim is by using alternative dispute resolution (ADR). This research paper shall cover mediation as a solution to medical negligence litigation since due to the loopholes in the current litigation system, many medical negligence victims fail to even bring their claim to the court because they fail to fulfill the requirements demanded by the fault-based system and because of the rigidness of the litigation system, many fail to seek the justice that they deserve. The flexibility and the fact that it consumes less time and money compared to litigation make mediation a mechanism that most people favor in solving medical negligence dispute. A comparative study with Australia and United Kingdom is done to show the need to change our ways to claim for medical negligence which is by resorting to mediation, instead of litigating it at the court. With the recent enforcement of the Mediation Act, it will be easier for victims in Malaysia to initiate a claim for medical negligence which is by choosing mediation since there will be some form of regulations that can be referred to. Thus, through this basic research paper, the victim of medical negligence may gain awareness of their rights to claim and seek remedy by way of mediation.